2012
DOI: 10.2463/mrms.11.185
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion- and T2-weighted MR Imaging of the Liver: Effect of Intravenous Administration of Gadoxetic Acid Disodium

Abstract: Purpose: We evaluated the eŠect of intravenous administration of gadoxetic acid disodium to hepatic lesions and liver parenchyma on T 2 -weighted (T 2 WI) and diŠusion-weighted imaging (DWI).Materials and Methods: One hundred and one consecutive patients with 259 hepatic lesions underwent T 2 WI and DWI (b-values of 500 and 1000 s/mm 2 ) before and after gadoxetic acid administration. We compared the ratio of signal intensity (SIR) of the liver parenchyma and hepatic lesions, the ratio of contrast intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Several researchers have suggested that T 2 -weighted imaging can be performed after gadoxetic acid injection, before the 20-min hepatobiliary as a means to shorten the overall protocol time. [36][37][38][39] Our T 2 measurements confirm that T 2 -weighted imaging after the injection of gadoxetic acid at either 0.025 or 0.05 mmol/kg should have minimal impact on T 2 contrast and can be used to shorten the overall protocol time. Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Several researchers have suggested that T 2 -weighted imaging can be performed after gadoxetic acid injection, before the 20-min hepatobiliary as a means to shorten the overall protocol time. [36][37][38][39] Our T 2 measurements confirm that T 2 -weighted imaging after the injection of gadoxetic acid at either 0.025 or 0.05 mmol/kg should have minimal impact on T 2 contrast and can be used to shorten the overall protocol time. Fig.…”
Section: Discussionmentioning
confidence: 65%
“…The T 2 * -shortening eŠect does not aŠect the image contrast of the liver on fast spin-echo T 2 -weighted fast spin-echo images and does not decrease tumor conspicuity or sensitivity on T 2 -weighted images. [35][36][37][38][39] This is not true, though, for the bile duct, in which a much higher concentration of excreted gadoxetic acid than in the liver parenchyma leads to a signiˆcant decrease in bile duct signals and degradation of T 2 -weighted MR cholangiopancreatography (MRCP). 40,41 Kim and colleagues, however, reported that post-contrast MRCP is acceptable if obtained within a few minutes of gadoxetic acid injection 42 because excretion of the contrast agent into the bile duct does not start until approximately 5 to 10 min after injection.…”
Section: Rules For the Hepatocyte Phase Delay Before Hepatocyte Phasementioning
confidence: 99%
“…HA is a benign neoplasm composed of hepatocytes and is treated with surgical resection if the HA is considered at high risk for spontaneous hemorrhage or malignant transformation. 30,32,39,58 Recent studies have provided evidence that gadoxetic acid-enhanced MR imaging in general and hepatocyte phase images in particular greatly facilitate the diŠerential diagnosis of these 2 lesions. Most FNHs are strongly enhanced during the arterial phase and show hyperintensity on hepatocyte phase images (Fig.…”
Section: Distinguishing Between Focal Nodular Hyperplasia (Fnh) and Hmentioning
confidence: 99%
See 1 more Smart Citation
“…An automated bolus detection algorithm (MR Smart Prep; GE Medical Systems, Milwaukee, WI, USA) or a fluoroscopic triggering (Bolus-Trak; Philips Medical Systems, Best, The Netherlands) was used to obtain an optimal hepatic arterial phase [13]. T2-weighted and DW sequences were obtained between the 3-min late and hepatobiliary phase to reduce the total examination time [14,15]. Other MRI parameters are shown in Table 1.…”
Section: Mr Imaging Protocolmentioning
confidence: 99%